Comparison of Digital Forensic Tools for Drug Trafficking Cases on Instagram Messenger using NIST Method - Nahdli, Muhammad Fahmi Mubarok; Riadi, Imam; Biddinika, Muhammad Kunta (Universitas Negeri Semarang, 2024)
Purpose: Cybercrime is an unlawful act that utilizes computer technology and the development of the internet. Cybercrime can occur on all electronic devices, including Android smartphones. Forensic handling, particularly mobile forensics, has become crucial in addressing drug trafficking cases conducted through Instagram. As the primary device for accessing Instagram, smartphones store digital data that can serve as evidence in investigations. This research aims to produce a more accurate comparison of results in analyzing Instagram Messenger data containing content related to drug trafficking. Methods: The digital evidence data used in this research included five types of data: text chat, account, image, audio, and image view once. The forensic tools for obtaining digital evidence were MOBILedit, Belkasoft, Mobile Forensic SPF, and Magnet Axiom. The method proposed in this research followed the NIST framework, which consists of four stages: collection, examination, analysis, and reporting. This research followed the NIST framework because it is widely recognized in the field of digital forensics and provides a comprehensive guideline for handling digital evidence. Result: Research results showed that Magnet Axiom had the best performance in digital forensic analysis, with a success rate of 74.1%. MOBILedit Forensic had a success rate of 62.5%, indicating lower performance. Mobile Forensic SPF had a success rate of 44.6%. In comparison, Belkasoft had the lowest success rate of 23.2%, showing that this software could be more effective in detecting and analyzing digital data than the others. Novelty: In this study, the analysis process was conducted using four digital forensic tools, each showing variations in terms of efficiency and effectiveness. Each tool has advantages and disadvantages regarding speed, accuracy, and ability to extract and manage data.